Hubungan Penerapan Atraumatic Care terhadap Kecemasan pada Anak yang Mengalami Hospitalisasi - Syukriadi Syukriadi; Nurul Amna; Dewi Ramadani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The impact of hospitalization on children is anxiety. To reduce this, it can be done by applying atraumatic care, which focuses on family-centered care in carrying out nursing actions. This study aims to determine the relationship of the application of atraumatic care to anxiety in children experiencing hospitalization at Pertamedika Ummi Rosnati Hospital Banda Aceh. This type of research is quantitative with a correlation study analytic design. Data collection was carried out on 5 to 26 July 2024. The population in the study were all children admitted to Pertamedika Ummi Rosnati Hospital Banda Aceh and a sample of 33 respondents with sampling techniques using purposive sampling. Data analysis using chi square test showed there was a relationship between the application of traumatic care and anxiety in children at Pertamedika Ummi Rosnati Hospital Banda Aceh with a p value of 0.000 (p <0.05). So it can be concluded that there is a relationship between the application of atraumatic care and anxiety in children who experience hospitalization. It is expected that parents know how to care for children while hospitalized so that children do not experience anxiety.